Loop electrosurgical excision procedure (LEEP) at Maharaj Nakorn Chiang Mai Hospital : Problems in pathologic evaluation - Khunamornpong S. (2014)
Background : Loop electrosurgical excision procedure (LEEP) is widely used in diagnosis and management of cervical lesions. Difficulties in histopathologic evaluation of LEEP specimens, particularly for the margin status, have been reported to be a significant disadvantage of the procedure. Method : The histologic slides of the specimens from 163 patients who underwent LEEP at Maharaj Nakorn Chiang Mai Hospital from August 1995 to November 1997 were retrospectively reviewed for the degree of thermal artefact and the margin status. Follow-up data after a 6-month-period were correlated with the margin status. Results : Thermal artefact was present in all cases (mild 51.5%, moderate 36.2%, and severe 12.3%). In only one case, histologic diagnosis of the lesion was not possible due to severe thermal artefact. Nine cases (5.5%) had non-evaluable margins due to either thermal artefact (7 cases) or improper orientation of fragmented tissue (2 cases). Of 90 cases with subsequent surgical specimens, residual diseases were present in 4 of 21 (19.0%) with negative LEEP margins, in 31 of 64 (48.4%) with positive margins, and in 4 of 5 (80.0%) with non-evaluable margins. Conclusions : Pathologic evaluation of the specimens from LEEP was limited in only a minority of cases. Thermal artefact was not a critical disadvantage of LEEP. The positive or negative margin status was correlated with the risk of residual disease.